2006
DOI: 10.1111/j.1600-6143.2006.01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression: Evolution in Practice and Trends, 1994–2004

Abstract: , 5.6a-i, 6.6a-i, 7.6a-i, 8.6a-i, 9.6a-i, 10.6a-i, 11.6a-i, 12.6a-i, 13.6a-i, 15.4a and b, 15.5a and b and 15.4-15.15. All of these tables may be found online at http://www.ustransplant.org. decline, reaching 13% for those who received a kidney in 2003, 48% of which cases were treated with antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
325
3
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(354 citation statements)
references
References 16 publications
9
325
3
9
Order By: Relevance
“…This favorable outcome compares with observed higher rejection rates for Groups TAC/SRL and CSA/ SRL, 30% (15/50) and 28% (14/50), respectively, and this difference clearly became significant once the multivariable effects of other prognosticators (race/ethnicity, recipient age, and donor age) were controlled. Although randomization of 50 patients per treatment arm only allowed reasonable statis- 1 Number of patients with the event (actuarial estimate of failure at 96 mo post-transplant Ϯ SE). 2 The P-values listed in this column represent the results of the logrank test (with 2 degrees of freedom) for any differences among the 3 treatment groups' hazard rates failure.…”
Section: Discussionmentioning
confidence: 99%
“…This favorable outcome compares with observed higher rejection rates for Groups TAC/SRL and CSA/ SRL, 30% (15/50) and 28% (14/50), respectively, and this difference clearly became significant once the multivariable effects of other prognosticators (race/ethnicity, recipient age, and donor age) were controlled. Although randomization of 50 patients per treatment arm only allowed reasonable statis- 1 Number of patients with the event (actuarial estimate of failure at 96 mo post-transplant Ϯ SE). 2 The P-values listed in this column represent the results of the logrank test (with 2 degrees of freedom) for any differences among the 3 treatment groups' hazard rates failure.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients transplanted in 2001, the change rate for Tac/MMF combination at 3 yr was 43% and that for SRL/MMF combination was up to 65%. 15 We have previously reported on the 2-yr safety and efficacy profile of SRL/steroids based regimens in combination with either low-dose Tac (group A) or MMF (group B) together with basiliximab induction therapy among live-donor renal allotransplant recipients in a prospective randomized study, and it was shown that the SRL/MMF regimen was safe regarding patient and graft survival and was associated with significant better renal function at 2 yr than the Tac/SRL regimen. 14 We hereby report on the long-term safety and efficacy profile of the same randomized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of the SRL/MMF combination has remained less than 1%. 15 We have previously reported on the safe and efficient use of SRL/MMF combination regimen together with steroids and basiliximab induction therapy in a short-term prospective randomized trial. 14 We hereby report on the safety and efficacy of the longer-term use of such a regimen in living donor renal transplant recipients.…”
mentioning
confidence: 99%
“…Use of induction therapy with ATG/IL-2 receptor blockers have further brought down the rejection rate [14,15]. Recent data reveals that 72% of renal transplant recipients today have tacrolimus, 81% MMF, 21% cyclosporine and 12 % sirolimus on their discharge prescription [1,16]. However, improvement in short term graft survival with tacrolimus has not transformed into long term graft or patient survival.…”
Section: Discussionmentioning
confidence: 99%